1978
DOI: 10.1007/bf00427386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morphine and chloropromazine on the detection of shock

Abstract: A discrete-trial, two-choice, 'yes-no' procedure was used to determine the extent to which the perceptual effects of compounds such as morphine and chlorpromazine (CPZ) can be attributed to drug-induced changes in ability to detect shock stimuli (sensitivity). Both morphine (4.0, 5.0, and 6.0 mg/kg) and CPZ (0.25, 0.50, and 1.0 mg/kg) significantly reduced accuracy and increased the times (i.e., lowered the speeds) to initiate trials and to make choice responses. The effects of morphine appeared to be somewhat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…These results suggest that morphine's effects differ when monkeys are responding differentially in the presence and absence of shock from when they are responding differentially in the presence of two different shock intensities. Previous studies, using rats, have also reported differences between results with the two types of discrimination tasks (Grilly & Genovese, 1979;Grilly et al, 1980;Lloyd et al, 1978;Poling et al, 1978).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results suggest that morphine's effects differ when monkeys are responding differentially in the presence and absence of shock from when they are responding differentially in the presence of two different shock intensities. Previous studies, using rats, have also reported differences between results with the two types of discrimination tasks (Grilly & Genovese, 1979;Grilly et al, 1980;Lloyd et al, 1978;Poling et al, 1978).…”
Section: Discussionmentioning
confidence: 90%
“…Other analgesic opioids such as methadone, pentazocine, and cyclazocine, as well as the nonopioid analgesic levonantradol, also decrease correct responding in the presence of shock (Dykstra, 1980(Dykstra, , 1981. In rats trained to respond differentially in the presence or absence of shock, morphine and other analgesics have similar effects (Hernandez & Appel, 1980;Lloyd, Appel, & McGowan, This research was supported by Grants DA02749 and MH14269. A preliminary report of this investigation appeared in Federation Proceedings (1982), 41 1978; Poling, Simmons, & Appel, 1978).…”
mentioning
confidence: 99%
“…Several investigations have attempted to assess the effects of various drugs on pain perception, utilizing discrete-trial, two-choice shock discrimination tasks (Dykstra, 1979, 1980; Genovese & Dykstra, 1984; Grilly, 1981; Grilly & Dugovics, 1982; Grilly, Genovese, & Nowak, 1980; Grilly, Nowak, Walsh, & Dugovics, 1981; Hernandez & Appel, 1979, 1980; Lineberry & Kulics, 1978; Lloyd, Appel, & McGowan, 1978; Poling, Simmons, & Appel, 1978). In these tasks one response is appropriate when the shock discriminative stimulus (S D ) is noxious, and another response is appropriate when the S D is either shock absence or a shock of lower intensity.…”
mentioning
confidence: 99%
“…In these tasks one response is appropriate when the shock discriminative stimulus (S D ) is noxious, and another response is appropriate when the S D is either shock absence or a shock of lower intensity. It has been suggested that by such tasks one is able to determine whether putative analgesic treatments alter the perceived intensity of shock as opposed to changing the organism's responsivity to shock (Chapman, 1977; Grilly & Genovese, 1979; Hernandez & Appel, 1979; Lloyd et al, 1978).…”
mentioning
confidence: 99%
“…Grilly of other studies using the shock discrimination paradigm, indicating that the direct behavioral effects of narcotics in shock discrimination tasks may not be related to their analgesic properties. For example, while some studies have noted that narcotics induce greater disruptions on shock presence S D trials than on shock absence (or lower intensity shock) trials (Lloyd et al 1978;Poling et al 1978;Dykstra 1979Dykstra , 1980, others have not observed differential effects (Grilly and Genovese 1979;Appel 1979, 1980;Grilly et al 1980;Grilly 1981 ;Genovese and Dykstra 1984). Furthermore, narcotics, in what are considered low to moderate analgesic doses for the respective species, have been shown to disrupt behavior in discrimination tasks involving non-noxious SD's (Hernandez and Appel 1979;Grilly et al 1980;West et al 1982;Koek and Slangen 1983 ;Nielson and Appel 1983).…”
mentioning
confidence: 99%